Modelling The Behavior of the Venture Capital Industry - Evidence from Egypt - Elsiefy, Elsayed; Foudah, Mohammed Lotfy (Archives of Business Research, 2015)
The objectives of this exploratory study are to investigate the behavior of the Venture Capital (VC) industry in Egypt, and to test whether there are relationships among the suggested dependent variables. We are studying the domestic VC industry through two dependent variables; i.e. 1) Patent Application Count representing the Innovation level, 2) Domestic Credit to Private Sector representing the private capital funding. Also we examine the international VC through the Foreign Direct Investment (FDI). We find positive significant relationship between the FDI and the Net Foreign Assets, the Gross Capital Formation and the Natural Gas Rents (% of GDP), while there is a negative significant relationship with the Broad Money. For the Domestic Credit to Private Sector, we find a positive significant relationship with the Merchandise Exports, the FDI and the Manufacturing Value Added (% of GDP), while we find a negative significant relationship with the Gross Savings (% of GDP). For the Patent Applications Count, we find a significant positive relationship with the Domestic Credit to Private Sector, the FDI, the Education Expenditure, the Gross Savings, the Industry Value Added and the Primary Education (Pupils) while negative significant relationship with GDP. We find that FDI is positively and significantly affecting both other dependent variables while both; i.e. FDI and Domestic Credit to Private sector, are positively and significantly affecting the Patent Applications Count.